The Effects of Firm Characteristics on Corporate Social Responsibility Disclosure Using Financial Performance as an Intervening Variabel - Rully Novira Elvandari; Supriyadi (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2023)
This study aims to determine the influence of company characteristics on corporate social responsibility disclosure by using financial performance as an intervening variable. This study used a quantitative approach. The secondary data were used as a data collection technique. The researchers used purposive sampling and a total of 126 data were collected as samples. This research was conducted on mining sector companies listed on the IDX in the period of 2019 to 2021. The results show that sales growth has a positive effect on financial performance, but the size of the company has a negative effect on financial performance. Financial performance has a positive effect on corporate social responsibility disclosure. Related to intervening variables, company growth positively affected corporate social responsibility disclosure through financial performance. However, the size of the company negatively affects the disclosure of corporate social responsibility through financial performance.